Mixed-dimensional heterostructures of hydrophobic/hydrophilic graphene foam for tunable hydrogen evolution reaction - Aslam, Sehrish; Sagar, Rizwan Ur Rehman; Kumar, Hitanshu; Zhang, Gaowei; Nosheen, Farhat; Namvari, Mina; Mahmood, Nasir; Zhang, Min; Qiu, Yejun (Chemosphere, 2020)
The synergetic effect of hydrophilic and hydrophobic carbon can be used to obtain tunable hydrogen evolution reaction (HER) at the interface. Herein, graphene oxide (GO-Hummers method) was coated on graphene foam (GF) synthesized via chemical vapor deposition to develop mixed-dimensional heterostructure for the observation of HER. The porosity of GF not only provides an optimized diffusion coefficient for better mass transport but also modified surface chemistry (GF/GO-hydrophobic/hydrophilic interface), which results in an onset potential 50 mV and overpotential of 450 mV to achieve the current density 10 mA/cm2. The surface analysis shows that inherent functional groups at the surface played a key role in tuning the activity of hybrid, providing a pathway to introduce non-corrosive electrodes for water splitting.
Keywords: grafit; hydrofobní a hydrofilní interakce; Carbon; Hydrogen; Hydrophobic and Hydrophilic Interactions; katalýza; Catalysis; elektrody; poréznost; Water; Porosity; uhlík; Electrodes; Graphite; vodík; voda